Dynamic Contracting with Intermediation: Operational, Governance, and Financial Engineering - GRYGLEWICZ, SEBASTIAN; MAYER, SIMON (Journal of Finance, 2023)
ABSTRACT Private equity funds intermediate investment and affect portfolio firm performance by actively engaging in operational, governance, and financial engineering. We study this type of intermediation in a dynamic agency model in which an active intermediary raises funds from outside investors and invests in a firm run by an agent. Optimal contracting addresses moral hazard at the intermediary and firm levels. The intermediary's incentives to affect firm performance are strongest after poor performance, while the agent's incentives are strongest after good performance. We also show how financial engineering, that is, financial contracting with outside investors, interacts with operational and governance engineering.